Creation of zebrafish knock‐in reporter lines in the nefma gene by Cas9‐mediated homologous recombination. Issue 1 (30th September 2019) - Eschstruth, Alexis; Schneider‐Maunoury, Sylvie; Giudicelli, François
Summary: CRISPR/Cas9‐based strategies are widely used for genome editing in many organisms, including zebrafish. Although most applications consist in introducing double strand break (DSB)‐induced mutations, it is also possible to use CRISPR/Cas9 to enhance homology directed repair (HDR) at a chosen genomic location to create knock‐ins with optimally controlled precision. Here, we describe the use of CRISPR/Cas9‐targeted DSB followed by HDR to generate zebrafish transgenic lines where exogenous coding sequences are added in the nefma gene, in frame with the endogenous coding sequence. The resulting knock‐in embryos express the added gene (fluorescent reporter or KalTA4 transactivator) specifically in the populations of neurons that express nefma, making them convenient tools for research on these populations.